Combined T2‐preparation and multidimensional outer volume suppression for coronary artery imaging with 3D cones trajectories. Issue 6 (5th November 2019) - Zeng, David Y.; Baron, Corey A.; Malavé, Mario O.; Kerr, Adam B.; Yang, Phillip C.; Hu, Bob S.; Nishimura, Dwight G.
Abstract : Purpose: To develop a modular magnetization preparation sequence for combined T2 ‐preparation and multidimensional outer volume suppression (OVS) for coronary artery imaging. Methods: A combined T2 ‐prepared 1D OVS sequence with fat saturation was defined to contain a 90°−60 180°60 composite nonselective tip‐down pulse, two 180°Y hard pulses for refocusing, and a −90° spectral‐spatial sinc tip‐up pulse. For 2D OVS, 2 modules were concatenated, selective in X and then Y. Bloch simulations predicted robustness of the sequence to B0 and B1 inhomogeneities. The proposed sequence was compared with a T2 ‐prepared 2D OVS sequence proposed by Luo et al, which uses a spatially selective 2D spiral tip‐up. The 2 sequences were compared in phantom studies and in vivo coronary artery imaging studies with a 3D cones trajectory. Results: Phantom results demonstrated superior OVS for the proposed sequence compared with the Luo sequence. In studies on 15 healthy volunteers, the proposed sequence had superior image edge profile acutance values compared with the Luo sequence for the right ( P < .05) and left ( P < .05) coronary arteries, suggesting superior vessel sharpness. The proposed sequence also had superior signal‐to‐noise ratio ( P < .05) and passband‐to‐stopband ratio ( P < .05). Reader scores and reader preference indicated superior coronary image quality of the proposed sequence for both the right ( P < .05) and left ( P < .05) coronary arteries. Conclusion: The proposed sequence with concatenated 1D spatially selective tip‐ups and integrated fat saturation has superior image quality and suppression compared with the Luo sequence with 2D spatially selective tip‐up.